Accounting and science : natural inquiry and commercial reason - Power, Michael (Professor of Accounting) (Cambridge studies in management, 1996)
"In recent years policy makers and scientists have become increasingly interested in the economics of science, and in particular in the relationship between accounting and science. This book, originally published as a special issue of the journal Science in Context, explores the intersections between the sociology and history of science and the sociology of accounting. Using a truly interdisciplinary approach the book draws attention to the constitutive role that practices of economic calculation in general, and of accounting in particular, play for the conduct of science and for the forms of economic life within which science is embedded. The contributors explore a number of issues, including the role of accounting as a distinctive form of administrative objectivity; conceptual exchanges between science and business administration; actuarial practices and their claims to scientificity; conceptions of the factory as a form of laboratory; accounting for research and development expenditure; the emerging role of patents in the physical sciences; and models of scientific accountability. One recurrent theme throughout the book is the manner in which forms of accounting practice construct possibilities for thought and action."--Jacket